Answer:
[tex]F(t)=Ts+(T0-Ts)^{e-0.2t[/tex]
Step-by-step explanation:
Newton's law of cooling states
"that the temperature of a body changes at a rate proportional to the difference in temperature between the body and its surroundings"
Newton's Law of Cooling is given by the formula
[tex]F(t)=Ts+(T0-Ts)^{e-kt[/tex]
Where
F( t ) is the temperature of the object at a given time t
T s is the surrounding temperature
T 0 is the initial temperature of the object
k is the constant
Given k=0.2
Hence the expression is
[tex]F(t)=Ts+(T0-Ts)^{e-0.2t[/tex]